Limb expression 1-like (LIX1L) protein promotes cholestatic liver injury by regulating bile acid metabolism - Li, Jie; Zhu, Xiaoyun; Zhang, Meihui; Zhang, Yanqiu; Ye, Shengtao; Leng, Yingrong; Yang, Ting; Kong, Lingyi; Zhang, Hao (Journal of hepatology, 2021)
Cholestatic liver diseases comprise a variety of disorders of bile formation and/or flow which generally result in progressive hepatobiliary injury. Regulation of bile acid (BA) synthesis and homeostasis is a promising strategy for the treatment of cholestatic liver disease. Limb expression 1-like protein (LIX1L) plays an important role in post-transcriptional gene regulation, yet its role in cholestatic liver injury remains unclear. LIX1L expression was studied in patients with primary sclerosing cholangitis (PSC) or primary biliary cholangitis (PBC), and 3 murine models of cholestasis (bile duct ligation [BDL], Mdr2 knockout [Mdr2-/-], and cholic acid [CA] feeding). Lix1l knockout mice were employed to investigate the function of LIX1L in cholestatic liver diseases. Chromatin immunoprecipitation assays were performed to determine whether Egr-1 bound to the Lix1l promoter. MiRNA expression profiling was analyzed by microarray. An adeno-associated virus (AAV)-mediated hepatic delivery system was used to identify the function of miR-191-3p in vivo. LIX1L expression was increased in the livers of patients with PSC and PBC, and in the 3 murine models, as well as in BA-stimulated primary mouse hepatocytes. BA-induced Lix1l upregulation was dependent on Egr-1, which served as a transcriptional activator. LIX1L deficiency attenuated cholestatic liver injury in BDL and Mdr2-/- mice. MiR-191-3p was the most reduced miRNA in livers of WT-BDL mice, while it was restored in Lix1l-/--BDL mice. MiR-191-3p targets and downregulates Lrh-1, thereby inhibiting Cyp7a1 and Cyp8b1 expression. AAV-mediated hepatic delivery of miR-191-3p significantly attenuated cholestatic liver injury in Mdr2-/- mice. LIX1L deficiency alleviates cholestatic liver injury by inhibiting BA synthesis. LIX1L functions as a nexus linking BA/Egr-1 and miR-191-3p/LRH-1 signaling. LIX1L and miR-191-3p may be promising targets for the treatment of BA-associated hepatobiliary diseases. Bile acid homeostasis can be impaired in cholestatic liver diseases. Our study identified a novel mechanism of positive feedback regulation in cholestasis. LIX1L and miR-191-3p represent potential therapeutic targets for cholestatic liver diseases. [Display omitted] •LIX1L was upregulated in cholestatic liver specimens from both patients and mouse models.•Bile acids triggered upregulation of Egr-1, which induced LIX1L expression.•LIX1L deficiency alleviated cholestatic liver injury by inhibiting bile acid synthesis.•Overexpression of miR-191-3p using AAV protected against cholestatic liver injury in mouse models.